Occurrence of aflatoxin M1 in human milk samples in Vojvodina, Serbia: Estimation of average daily intake by babies. Issue 1 (2nd January 2017) - Radonić, Jelena R.; Kocić Tanackov, Sunčica D.; Mihajlović, Ivana J.; Grujić, Zorica S.; Vojinović Miloradov, Mirjana B.; Škrinjar, Marija M.; Turk Sekulić, Maja M.
ABSTRACT: The objectives of the study were to determine the aflatoxin M1 content in human milk samples in Vojvodina, Serbia, and to assess the risk of infants' exposure to aflatoxins food contamination. The growth of Aspergillus flavus and production of aflatoxin B1 in corn samples resulted in higher concentrations of AFM1 in milk and dairy products in 2013, indicating higher concentrations of AFM1 in human milk samples in 2013 and 2014 in Serbia. A total number of 60 samples of human milk (colostrum and breast milk collected 4–8 months after delivery) were analyzed for the presence of AFM1 using the Enzyme Linked Immunosorbent Assay method. The estimated daily intake of AFM1 through breastfeeding was calculated for the colostrum samples using an average intake of 60 mL/kg body weight (b.w.)/day on the third day of lactation. All breast milk collected 4–8 months after delivery and 36.4% of colostrum samples were contaminated with AFM1. The greatest percentage of contaminated colostrum (85%) and all samples of breast milk collected 4–8 months after delivery had AFM1 concentration above maximum allowable concentration according to the Regulation on health safety of dietetic products. The mean daily intake of AFM1 in colostrum was 2.65 ng/kg bw/day. Results of our study indicate the high risk of infants' exposure, who are at the early stage of development and vulnerable to toxic contaminants.